Knowledge, Evidence, and Policymaking - Einfeld, Colette. author. (orcid)0000-0001-8324-4403 Link aut Link
VIII, 160 p.
Keywords: “Colette Einfeld brings a much-needed critical eye to behavioural insights, one of the most popular policy ‘solutions’ to emerge in contemporary times. In this ground-breaking new book, she tackles not just questions of the effectiveness (or not) of these approaches, but also grapples with the ethical and contextual dimensions. In laying out the mixed evidence for behavioural insights in practice, Einfeld sheds much-needed light on why governments around the world have been so captured by these ideas. For those interested in understanding the influence and impact of knowledge in practice, Einfeld brings us a thought-provoking and timely contribution.” —Janine O'Flynn, Professor, Director of the Crawford School of Public Policy, Australian National University, Australia. “A wonderful book that illuminates the different knowledges at play in the development and enacting of public policy instruments. Through careful investigation and analysis Einfeld illustrates the different uses of knowledge and their impact on policy efficacy. A must read for critical scholars and practitioners interested in understanding why policy instruments don't always 'work'.” —Helen Sullivan, Professor, Dean of the College of Asia and the Pacific, Australian National University, Australia. This book provides an insightful and nuanced account of the roles of knowledge and evidence in behavioural science practices. Utilising evidence from Australia, it draws together the fields of evidence-based policymaking and behavioural insights in order to examine how policy actors negotiate the use of scientific evidence, knowledge, lived experience, and ethics in policymaking. It also considers the ways in which different knowledges can ‘compete’ in public policy, and the roles of policymakers in that competition. Offering insights for both evidence-based policy processes and the application of behavioural insights more generally, the book is a valuable resource for academics and practitioners interested in behavioural sciences, and the impact of different types of evidence in policymaking. Colette Einfeld is a Research Fellow at the College of Asia and the Pacific, Australian National University, Australia. Her research focusses on knowledge and evidence in policy practices in Australia and Asia.